2017
DOI: 10.1590/1413-81232017222.13622015
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do Programa “Bolsa Família” sobre a qualidade da dieta das famílias de Pernambuco no Brasil

Abstract: This article analyzes the impact of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
0
12
0
7
Order By: Relevance
“…Possible short-term impacts include changes in nutritional status in adults, through reduced salt and ultraprocessed foods intake, increased consumption of foods with high nutrient content, and increases in overall energy intake. [20][21][22][23][24][25] BFP can also affect the socioeconomic conditions of the household, including more working hours, better jobs and higher income. [26][27][28] Effects of CCTs that may be observed at in the medium term include those intermediated by the health conditionalities of BFP, such as increased healthcare utilisation.…”
Section: Logic Modelmentioning
confidence: 99%
“…Possible short-term impacts include changes in nutritional status in adults, through reduced salt and ultraprocessed foods intake, increased consumption of foods with high nutrient content, and increases in overall energy intake. [20][21][22][23][24][25] BFP can also affect the socioeconomic conditions of the household, including more working hours, better jobs and higher income. [26][27][28] Effects of CCTs that may be observed at in the medium term include those intermediated by the health conditionalities of BFP, such as increased healthcare utilisation.…”
Section: Logic Modelmentioning
confidence: 99%
“…28,5,4 The average amount of food group portion consumption is generally higher in participating households than in nonparticipating households, and there is a positive effect on income transfers on the diet quality of Pernambuco family units, showing the efficiency of PBF to improve the nutrition of beneficiary families. 2 The main nutritional disorders in children, such as excessive weight and chronic malnutrition, show a scenario of nutritional transition and point out the need for strengthening food and nutritional monitoring actions and the implementation of programs on health and nutrition policies. 29,30 In a research project conducted in Belo Horizonte with the objective of evaluating the nutritional profile of preschool children, whether or not benefited by the PBF, enrolled in public daycare centers in the Eastern Region of Belo Horizonte -MG, it was found that, comparing beneficiary and non-beneficiary children in terms of the nutritional aspect, there was no difference and most of them were eutrophic.…”
Section: Table Analysismentioning
confidence: 99%
“…It was observed that after the implementation of the program, food consumption by the poorest families increased by about R $ 388 per year after receiving the benefit, but there was no evidence of nutritional improvement. 2 Regarding poverty reduction, there was a 16% reduction in the country's poverty rates, from 1999 to 2009, attributed to the implementation of the PBF. 3 Although access to food has improved, healthy food consumption has still been limited by job instability and the low income of much of the beneficiary population of this program.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, aiming to favor quality of life (Coelho & Melo, 2017;Ribas-Prado et al, 2016), several developing countries have used income support programs to reduce poverty and social inequality (Monnerat et al, 2007;Oliveira et al, 2011a;Roque et al, 2015;Almeida e Silva, 2016). In Brazil, such strategy is performed through social assistance programs such as the Bolsa Família (Sperandio e Priore et al, 2015), which is considered the most extensive income support program directed to families in poverty or extreme poverty conditions (Brasil, 2018).…”
Section: Introductionmentioning
confidence: 99%